The Role of Balanced Nutrition for the Recovery of COVID-19 Patients Undergoing Self-Isolation - Heny Yuniarti; Reza Adityas Trisnadi (Indonesian Journal of Community Services, 2022)
Coronavirus (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. Not all COVID-19 patients are reported to have severe symptoms. There are also patients who are asymptomatic or with mild symptoms who only need rest and self-isolation. Self-isolation is an attempt to separate a person confirmed COVID-19 with or without symptoms, from a healthy person which aim is to reduce the risk of transmission. Nutritional intake in patients with COVID-19 includes energy needs from macronutrient, micronutrients, fluids and electrolytes. A balanced diet can support a strong immune system and help fight viral infections. In this activity, the method used was whatsApp media or android /web-based applications. Patients are classified into 3 groups, namely asymptomatic groups or mild symptoms, without decreased oxygen saturation (green group), patients with moderate symptoms, oxygen saturation still above 95% (yellow group), patients with severe symptoms and saturation below 95% (red group). Virtual consultations are conducted with the aim of reminding a balanced nutrition intake in patients, guiding cough techniques and warning signs of COVID-19. This activity provided lunch support consisting of rice, vegetables, animal protein, side dishes and fruit that can hasten healing from COVID-19.